Students’ perceptions of adopting songs for English online learning in Indonesian tertiary education - Eka Wulandari; Yuyun Putri Mandasari (Erudita: Journal of English Language Teaching, 2021)
The pandemic situation in the last two years has forced us to move almost all activities online, including our teaching and learning activities. This creates challenges for teachers to discover suitable techniques or media to motivate students to keep being active in online class interaction. One of the possible media that can be used is songs; a media which is already popular among the youths. This paper presented a data survey towards 107 female students aged 19-20 years old from one of the midwifery academies situated in Central Java, Indonesia. This study used an online questionnaire form. There were 18 items in the questionnaire and the data consisted of demographic data and students’ perception towards the use of songs for improving their skills in English. The data were presented in the percentage data and analyzed using descriptive explanation. The result showed that the students’ perception on songs as media for English online learning achieved positive perception on all items. Referring to this finding, teachers can consider using songs for English online learning in order to create an attractive and interactive online learning process.